Model Pemberdayaan UMKM Berbasis E-Bisnis: Solusi Strategis Penanggulangan Kemiskinan melalui Peluang Ekonomi Lokal - Ahmad Zaki Rasyandra; Yusuf Rusmawardani; Niken Febriyati; Jihan Sabita (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Micro, Small, and Medium Enterprises (MSMEs) are essential in fostering economic development, generating job opportunities, and enhancing the well-being of communities. Nonetheless, various obstacles such as restricted market access, minimal digital knowledge, lack of funding, and inadequate management skills continue to impede the progress of MSMEs. Simultaneously, the advancements in information and communication technology through e-business implementation present considerable chances for MSMEs to increase their competitiveness and broaden their market presence. This research seeks to examine an e-business-oriented MSME empowerment framework as a strategic method to bolster local economic possibilities while aiding in poverty reduction initiatives. The study utilizes a qualitative descriptive methodology, relying on library research techniques that involve analyzing scientific journal articles, books, government documents, and pertinent publications from global organizations. The results reveal that embracing e-business enhances operational effectiveness, broadens market accessibility, boosts sales revenue, fortifies business competitiveness, and creates additional job prospects. The success of this empowerment framework relies on joint efforts among government agencies, academic institutions, the private sector, financial organizations, and local communities focusing on enhancing digital literacy, providing business guidance, ensuring financial inclusion, and developing digital infrastructure. Consequently, the e-business-oriented MSME empowerment framework presents a strategic and sustainable solution for reinforcing local economies, elevating community welfare, and promoting inclusive economic growth and enduring poverty alleviation.